Challenges of Rendering Chauvinism into Arabic: Implications for Dictionary Users and Translation Equivalence - al-kuran, Mohammad (Jordan Journal of Modern Languages & Literatures, 2024)
Bilingual dictionaries sometimes do not satisfy the needs of dictionary users because they offer partial equivalents or incomplete information. This status does not avail the users who seek to immediately retrieve the required information. The users presume that language entries in bilingual dictionaries are communicative equivalents that can be used to translate specific occurrences of the source language item. If the semantic and communicative translation does not hold between the SL and TL, the user will not be able to render the item in question successfully. This paper examines the target language equivalents for ‘chauvinism in English –Arabic dictionaries, namely the Oxford English-Arabic Dictionary (2014); Al-Mawrid, English- Arabic (2006); Al-Muɣni al-Kabiːr (1995); The Oxford Word Power (2006); The Dictionary, English-Arabic (2004), as a representative sample. These dictionaries do not catch the broad range of the concept that covers many sorts of claims and social attitudes in its native linguistic sources. To make up for this deficiency, the paper highlights the appropriate strategies that translators can use to render this concept communicatively into Arabic. The study is based on the communicative functional approach which assumes that dictionary meaning is insufficient to resolve potential ambiguities and that the contexts are necessary to unpack specific senses or connotations of the item. This deficiency has an impact on the translator’s choice of strategy to meet the target readers’ needs. Finally, strategies and suggestions for helping to achieve equivalence in bilingual dictionaries are discussed.